Improved stability of a phase change memory device using Ge-doped SbTe at varying ambient temperature - Wu, Zhe; Lee, Suyoun; Park, Young-Wook; Ahn, Hyung-Woo; Jeong, Doo Seok; Jeong, Jeung-hyun; No, Kwangsoo; Cheong, Byung-ki (AMER INST PHYSICS, 2010)
Ge-doped SbTe (Ge-ST) was compared with Ge2Sb2Te5 (GST) for its potential use in the phase-change memory with improved stability at varying ambient temperature (T-A). Device characteristics such as RESET current, RESET resistance, and SET resistance of Ge-ST devices were found to vary significantly less with T-A than those of GST devices. From measured carrier density, mobility, and optical band gaps, these findings are interpreted to derive from a metallic nature of the crystalline Ge-ST in contrast with a semiconducting nature of the crystalline GST as well as a relatively weaker covalent bonding in amorphous Ge-ST.